2009
DOI: 10.1002/poc.1518
|View full text |Cite
|
Sign up to set email alerts
|

Mixed valence of a delocalized system: a resonance Raman study of the tetracyanoquinodimethane radical anion

Abstract: The optical absorption spectrum and resonance Raman enhancement of the lowest energy absorption band of K R 7,7,8,8-tetracyanoquinodimethane S (TCNQ) are reported and examined in the mixed valence (MV) framework. The absorption spectrum is assigned, in accordance with previous work, using Koopmans-based calculations and the neighboring orbital model is constructed from the adiabatic orbital energies. Calculated fits of the lowest energy absorption band and the corresponding resonance Raman enhancement profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…We have discussed the neighboring orbital model previously . The molecular orbitals involved in the transitions of interest are composed of three groups of atomic orbitals: the nitrogen p z orbital, three oxygen p z orbitals that form three linear combinations of a 2 ″ e″ symmetry, and the single‐node aryl pi orbitals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have discussed the neighboring orbital model previously . The molecular orbitals involved in the transitions of interest are composed of three groups of atomic orbitals: the nitrogen p z orbital, three oxygen p z orbitals that form three linear combinations of a 2 ″ e″ symmetry, and the single‐node aryl pi orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…We have discussed the neighboring orbital model previously. [4,[44][45][46][47][48][49][50][51][52][53] The molecular orbitals involved in the transitions of interest are composed of three groups of atomic orbitals: the nitrogen p z orbital, three oxygen p z orbitals that form three linear combinations of a 2 00 e 00 symmetry, and the single-node aryl pi orbitals. Each aryl group has two degenerate single node MOs (in addition to the p nodal plane) that are close enough in energy to strongly interact with the nitrogen and oxygen p z orbitals.…”
Section: Neighboring Orbital Model Interpretationmentioning
confidence: 99%
“…The enhancement of the MNA bands at 1205 and 1155 cm –1 by 488 nm line suggests that the next electronic transition originates from π–π* excitation in the phenyl ring. According to the time-dependent theory, ,,, the modes of vibrations giving the most intense bands in Raman and RR spectra are responsible for the largest distortions (largest displacements of the excited-state potential surface along their normal coordinates). , The calculated (at 0 K) distances between chosen atoms in the MNA molecule ground and first excited states (in parentheses), differing mostly, are as follows: C–N(O 2 ) 1.447 Ǻ (1.440 Ǻ), C–N(H 2 ) 1.369 Ǻ (1.379 Ǻ), N–O 1.266 Ǻ (1.347 Ǻ), N–O′ 1.265 Ǻ (1.425 Ǻ), and C5–C6 1.380 Ǻ (1.389 Ǻ).…”
Section: Resultsmentioning
confidence: 99%
“…1 r 12 ) 1 -erf(ωr 12 ) r 12 + erf(ωr 12 ) r 12 (12) chosen to be 0.30a 0 -1 . This value is based on previous applications where it was shown that this value leads to the best performance for excited-state properties, such as excitation energies.…”
Section: Computational Detailsmentioning
confidence: 99%